GSTP1 improves CAR-T cell proliferation and cytotoxicity to combat lymphoma - Xu, Guangsong; Wang, Jiani; Qu, Yuliang; Ning, Jing; Zhang, Yanting; Xu, Guangxian; Shi, Yunxia; Li, Ying; Guo, Le; Han, Xuebo; Wang, Hongxia (Frontiers in Immunology, 2025)
IntroductionThe exhaustion of chimeric antigen receptor T cells (CAR-T) hampers the efficacy of CAR-T cell therapy. Persistent antigen stimulation in T cells results in a surge of intracellular reactive oxygen species (ROS). ROS, as mitochondrial metabolites, alter the integrity of the mitochondrial membrane and promote T-cell exhaustion. Glutathione S-transferase Pi-1 (GSTP1), a member of the glutathione S-transferase family, is an important enzyme in the intracellular clearance of ROS. Overexpression of GSTP1 may enhance the antitumor capability of CAR-T cells.MethodsThe correlations between GSTP1 and genes related to T-cell exhaustion were analyzed using the TIMER database. Peripheral blood mononuclear cells (PBMCs) were collected from patients with hematologic malignancies (n = 61) and healthy donors (n = 45) to measure GSTP1, B-lymphocyte maturation protein 1 (BLIMP1), and programmed cell death protein 1 (PD-1) expression by qRT-PCR. A T-cell exhaustion model was established to assess GSTP1 expression by Western blotting. The dual-luciferase assay and ChIP-qPCR were used to determine whether the transcription factor BLIMP1 negatively regulated the activity of the GSTP1 promoter. CD19 CAR-T, GSTP1 overexpressing CAR-T (GSTP1 CAR-T), and GSTP1-knockdown CAR-T (shGSTP1 CAR-T) cells were generated to evaluate their antitumor capacity.ResultsGSTP1 expression was downregulated when BLIMP1 and PD-1 were upregulated in PBMCs of cancer patients and in the in vitro T-cell exhaustion model. Meanwhile, ROS levels in the T-cell exhaustion model increased. Mechanistically, the BLIMP1 transcription factor negatively regulated the activity of the GSTP1 promoter. Based on these findings, we engineered GSTP1 CAR-T cells, which exhibited improved functionality. GSTP1 CAR-T cells increased the TEMRA population, enhanced proliferation and cytotoxicity, elevated antioxidant capacity, increased IL-2 and IFN-γ secretion, reduced the expression of immune checkpoints, and decreased apoptosis. In vivo, the residual levels of GSTP1 CAR-T cells were higher than those of Cluster of Differentiation 19 (CD19) CAR-T cells and shGSTP1 CAR-T cells, indicating that GSTP1 CAR-T cells exhibited a strong antitumor capacity.ConclusionBLIMP1 directly suppressed GSTP1 transcription, whereas GSTP1 overexpression enhanced the antitumor capacity of CAR-T cells and maintained redox homeostasis, providing a novel therapeutic strategy to improve CAR-T cell immunotherapy.